Non-glandular trichomes of Solanum carolinense deter feeding by Manduca sexta caterpillars and cause damage to the gut peritrophic matrix. Issue 1849 (22nd February 2017) - Kariyat, Rupesh R.; Smith, Jason D.; Stephenson, Andrew G.; De Moraes, Consuelo M.; Mescher, Mark C.
Abstract : Plant trichomes constitute a first line of defence against insect herbivores. The pre- and post-ingestive defensive functions of glandular trichomes are well documented and include direct toxicity, adhesion, antinutrition and defence gene induction. By contrast, the defensive functions of non-glandular trichomes are less well characterized, although these structures are thought to serve as physical barriers that impede herbivore feeding and movement. We experimentally varied the density of stellate non-glandular trichomes in several ways to explore their pre- and post-ingestive effects on herbivores. Larvae of Manduca sexta (Sphingidae) initiated feeding faster and gained more weight on Solanum carolinense (Solanaceae) leaves having lower trichome densities (or experimentally removed trichomes) than on leaves having higher trichome densities. Adding trichomes to artificial diet also deterred feeding and adversely affected caterpillar growth relative to controls. Scanning electron and light microscopy revealed that the ingestion of stellate trichomes by M. sexta caterpillars caused extensive damage to the peritrophic membrane, a gut lining that is essential to digestion and pathogen isolation. These findings suggest that, in addition to acting as a physical barrier to deter feeding, trichomes can inhibit caterpillar growth and development via post-ingestive effects.